The Eternal Crossroads : The Art of Flannery O'Connor - Driskell, Leon V., 1932- (Book collections on Project MUSE., 1971)
Flannery O'Connor was a writer of extraordinary power and virtuosity. Her strong supple prose blends humor, pathos, satire, and grotesquerie which leads the reader to the evil at the center of the self's labyrinth. There, she confronts that evil with originality and power, pulling the reader into consideration of the terrifying dependencies of love in the recesses of the heart. This study focuses on Flannery O'Connor's sense of the coincidence of the eternal and cosmic with worldly time and place -- ""the eternal crossroads""--And how that sense controls and infuses her fiction